2017
DOI: 10.1007/s00373-017-1792-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Dominating Graphs

Abstract: The k-dominating graph D k (G) of a graph G is defined on the vertex set consisting of dominating sets of G with cardinality at most k, two such sets being adjacent if they differ by either adding or deleting a single vertex. A graph is a dominating graph if it is isomorphic to D k (G) for some graph G and some positive integer k. Answering a question of Haas and Seyffarth for graphs without isolates, it is proved that if G is such a graph of order n ≥ 2 and with G ∼ = D k (G), then k = 2 and G = K 1,n−1 for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The concept of k-dominating graphs was introduced by Haas and Seyffarth [34] in 2014. This paper stimulated the work of Alikhani, Fatehi, and Klavžar [1], Mynhardt, Roux, and Teshima [51], Suzuki, Mouawad, and Nishimura [56], and their own follow-up paper [35].…”
Section: The K-dominating Graphmentioning
confidence: 76%
See 2 more Smart Citations
“…The concept of k-dominating graphs was introduced by Haas and Seyffarth [34] in 2014. This paper stimulated the work of Alikhani, Fatehi, and Klavžar [1], Mynhardt, Roux, and Teshima [51], Suzuki, Mouawad, and Nishimura [56], and their own follow-up paper [35].…”
Section: The K-dominating Graphmentioning
confidence: 76%
“…Haas and Seyffarth [34] considered the question of which graphs are realisable as k-dominating graphs and observed that for n ≥ 4, D 2 (K 1,n−1 ) = K 1,n−1 . Alikhani et al [1] proved that these stars are the only graphs with this property, i.e. if G is a graph of order n with no isolated vertices such that n ≥ 2, δ ≥ 1, and G ∼ = D k (G), then k = 2 and G ∼ = K 1,n−1 for some n ≥ 4.…”
Section: The K-dominating Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have also been obtained for SHORTEST PATH RECONFIGURATION [107], INDEPENDENT SET RECONFIGURATION [108], and TOKEN SLIDING [109], as defined in Section 9.2. Examples of properties that have been studied include chromatic number [109], Hamiltonicity [20,106,[109][110][111][112], and girth [107,113], often in service of determining limits on the classes of graphs represented by reconfiguration graphs [108,[113][114][115]. For a source problem in which the instance is a graph, one can also identify when the reconfiguration graph for an instance is isomorphic to the instance itself [114,115].…”
Section: Other Structural Problemsmentioning
confidence: 99%
“…Results have also been obtained for SHORTEST PATH RECONFIGURATION [107], INDEPENDENT SET RECONFIGURATION [108], and TOKEN SLIDING [109], as defined in Section 9.2. Examples of properties that have been studied include chromatic number [109], Hamiltonicity [20,106,[109][110][111][112], and girth [107,113], often in service of determining limits on the classes of graphs represented by reconfiguration graphs [108,[113][114][115]. For a source problem in which the instance is a graph, one can also identify when the reconfiguration graph for an instance is isomorphic to the instance itself [114,115].…”
Section: Other Structural Problemsmentioning
confidence: 99%